Climate change impacts under representative concentration pathway scenarios on streamflow and droughts of basins in the Brazilian Cerrado biome. (28th October 2019) - Rodrigues, Jéssica A. M.; Viola, Marcelo R.; Alvarenga, Lívia A.; de Mello, Carlos R.; Chou, Sin C.; de Oliveira, Vinícius A.; Uddameri, Venkatesh; Morais, Marco A. V.
Abstract: Brazilian Cerrado biome is the largest and richest tropical savanna in the world. In order to understand the effects of climate changes on the hydrology of the Cerrado basins, this paper investigates the hydrological impacts of climate change throughout the 21st century under different emissions scenarios on the streamflow and on the droughts in the Sono, Manuel Alves da Natividade and Palma basins, located in the Brazilian Cerrado. For this purpose, the SWAT hydrological model driven by the downscaling of the HadGEM2‐ES and MIROC5 global climate models associated with RCP4.5 and RCP8.5 scenarios were used in three time slices (2011–2040, 2041–2070 and 2071–2099). The Standardized Precipitation Index (SPI) and the Standardized Streamflow Index (SSFI) were used to characterize droughts. In general, the results showed that the duration, intensity and frequency of the meteorological and hydrological droughts are expected to increase during the future periods. However, the hydrological droughts are projected to be larger than the meteorological droughts. Reductions in the streamflow are indicated in all future time slices and under both RCPs, especially, during dry periods, which may cause negative impacts in the ecological functions of the Cerrado biome, risk for reduction of the recharge of aquifers and risk for the electric energy production in northern Brazil. Abstract : This study investigates the impacts of climate change in the Sono, Manuel Alves da Natividade and Palma basins, in the Brazilian Cerrado by means of hydrologic simulations. The results show an increase of the hydrological and meteorological droughts and a significant reduction in the streamflow throughout the 21st century, for both RCP4.5 and RCP8.5, which may bring risks for the ecology of the Cerrado biome and for the electric energy production in northern Brazil.